Promoting Tenth-Grade Students’ Metacognition Using Design-Based Learning: A Mixed-Methods Case Study - Ladachart, Luecha; Khamlarsai, Sirinapa (Journal of Inclusive and Innovative Education, 2022)
This article presents results of a mixed-methods case study that examined metacognition of six female tenth-grade students, who were purposefully selected, before and after engaging in design-based learning activities. The researchers gathered quantitative data using a five-point Likert scale comprising 12 items measuring three aspects of metacognition (i.e., planning, monitoring, and self-regulation). Moreover, the researchers collected qualitative data by audio recording the students’ verbal interactions during the learning activities and conducting semi-structured interviews with the students. The researchers analyzed the quantitative data using statistical methods and then analyzed the qualitative data using a method of content analysis. The research results revealed that, when considering all three aspects together, the students did not significantly developed metacognition. However, when considering each aspect of metacognition separately, the students significantly developed the aspect regarding monitoring their own learning.